The complete mitochondrial genome of Muscina pascuorum (Diptera: Muscidae) - Jingjing Huang; Zixiang Ni; Hua Wang; Li Zhang; Jie Yan; Shengbin Bai (Mitochondrial DNA. Part B. Resources, 2021)
Muscina pascuorum (Diptera: Muscidae) represents an important hygiene pest. The complete mitochondrial genome (mitogenome) of M. pascuorum was first sequenced and annotated in this study. The full length of mitogenome was 14, 940 bp, consisting of 13 protein-coding genes (PCGs), two ribosomal RNA (rRNA), 22 transfer RNA (tRNA), and one AT-rich region. The nucleotide content of these flies was 40.0% A, 13.2% C, 9.1% G, and 37.6% T. This study illustrates that the arrangement of the genes was identical to classical metazoans. Besides, the phylogenetic analyses indicated that the branch of M. pascuorum was clustered separately from the common three Muscina spp in the tree. This genome provides an essential reference for understanding the phylogenetic relationships of Muscidae.